Macroeconomics - Samuelson, Paul A. (McGraw-Hill, 1995)
Barro uses a unique market-clearing approach to analyze and explain macroeconomic theory. This edition has been reorganized to cover applications alongside the appropriate theory, focusing on the latest advances in economic growth. New software is included with the text.